Coping with being cooped up: Social distancing during COVID-19 among 60+ in the United States - Kerstin Gerst Emerson (Pan American Health Organization, 2020)
Objectives. This study examined the impact of sheltering in place and social distancing among adults aged 60 and older during the 2020 outbreak of COVID-19 in the United States. Methods. Using convenience sampling respondents were asked to complete a web-administered survey to explore impact of social distancing on loneliness, stress, and behavioral changes. The analytic sample consisted of 833 responses of persons aged 60 and older. Results. A large portion reported being stressed (36%), and/or being lonely (42.5%). Nearly 1/3 stated that their sense of loneliness increased during the time of social distancing. Respondents reported engaging in more solitary activity (and fewer in-person activities), using email and text messages more than usual, and spending more time on computers/tablet than usual. Approximately 2/3 reported using more social media than usual. These differed significantly by younger (age 60-70) and older (71+) respondents. Additionally, changes in physical activity, drinking, recreational drug use and sleeping pattern changes differed by age. Conclusions. Social distancing has significant consequences on loneliness and health behaviors among adults in the United States, many of which differ by age group. Results have implications for continued shelter in place practices, but also for any older adult that may be homebound for other reasons.